From online symphonies to MusiMOO: Some creative uses of the internet in music and education. - Hugill, Andrew (Contemporary Music Review, 2005)
This article describes several projects which make creative use of the Internet in music and education, undertaken by the author since 1995. These range from collaborative composition projects to the use of virtual environments. Participants have included schoolchildren, university undergraduate and postgraduate students, adult learners, musicians and composers. In all cases, the Internet was used to explore new methods of music-making, composition and performance, along with analysis and discussion of compositional and cultural issues in relation to digital music and culture in general. It is intended that this account should illustrate the range and diversity of potential uses of the Internet in this field.